A Quantitative Approach to Microvariation: Negative Marking in Central Romance - Diego Pescarini (Languages, 2022)
This work presents an exploratory data analysis of the syntactic distribution of pre- and postverbal negation (N1 and N2) in a corpus of data gathered from two linguistic atlases, the Linguistic Atlas of France (ALF) and the Italo-Swiss Atlas (AIS). Metadata concerning the distribution of N1 and N2 across dialects and syntactic contexts are analyzed with the r package Rbrul. Multiple logistic regression allows us to assess how independent variables affect the presence/absence of N1/N2. Geographical and grammatical factors are examined; the latter concern mainly clause typing and negative concord, i.e., the co-occurrence of clausal negation and a negative word. The data from the two atlases are first analyzed separately and eventually merged in order to strengthen the statistical significance. Both geographical and grammatical factors prove to be significant. In particular, the preliminary findings show that N1 is more likely retained in sentences containing another negative word, the incidence of N1 varies according to the type of co-occurring negative word, and veridicality has a mild effect on N2 but not N1.